1995
DOI: 10.2307/3283917
|View full text |Cite
|
Sign up to set email alerts
|

Hemocytes of Schistosome-Resistant and -Susceptible Biomphalaria glabrata Recognize Different Antigens on the Surface of Schistosoma mansoni Sporocysts

Abstract: A cytoadherence assay was used to determine whether antibodies to plasma and hemocyte components of Schistosoma mansoni-susceptible (M-line) and -resistant (10-R2, 13-16-R1) strains of Biomphalaria glabrata affected attachment of hemocytes to chemically fixed schistosome sporocysts differentially. Experiments used purified, intact IgG and purified Fab fragments of each antibody. Indirect fluorescent antibody tests confirmed that the intact purified IgG to plasma and hemocytes from the 3 strains of snails bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This phenomenon indicates that Type II cells (round cells) are young cells which still have the capacity to develop and change into Type I cells which are active in phagocytosis. Biomphalaria glabrata can be classified into two strains; a resistant strain and a susceptible strain for Schistosoma mansoni infection, and hemocytes of schistosome-resistant and susceptible Biomphalaria glabrata can recognize different antigens on the surface of the parasites (Anger and Granath, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon indicates that Type II cells (round cells) are young cells which still have the capacity to develop and change into Type I cells which are active in phagocytosis. Biomphalaria glabrata can be classified into two strains; a resistant strain and a susceptible strain for Schistosoma mansoni infection, and hemocytes of schistosome-resistant and susceptible Biomphalaria glabrata can recognize different antigens on the surface of the parasites (Anger and Granath, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The subtleties of the intermediate host-parasite relationship, although recognized, are not fully understood, but evidently should be viewed in terms of compatibility or incompatibility (Arfaa et al ., 1989;Joubert et al ., 1991;Anger and Granath, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…These include, but are not limited to, differences in lectin‐binding specificities (Schoenberg & Cheng ; Martins‐Souza et al. ), lysosomal enzyme content (Granath & Yoshino ), cell surface antigens (Granath & Aspevig ; Agner & Granath ), cell surface polypeptides (Coustau & Yoshino ), production of hydrogen peroxide following stimulation by phorbol myristate acetate (Bender et al. ), levels of cytosolic superoxide dismutase (Bender et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, many investigators also have shown qualitative and quantitative differences in functional characteristics between hemocytes of resistant and susceptible snails that may be relevant to sporocyst recognition, adherence, and killing. These include, but are not limited to, differences in lectin-binding specificities (Schoenberg & Cheng 1980;Martins-Souza et al 2006), lysosomal enzyme content (Granath & Yoshino 1983), cell surface antigens (Granath & Aspevig 1993;Agner & Granath 1995), cell surface polypeptides (Coustau & Yoshino 1994), production of hydrogen peroxide following stimulation by phorbol myristate acetate (Bender et al 2005), levels of cytosolic superoxide dismutase (Bender et al 2007), patterns of gene expression following exposure to Schistosoma mansoni or its excretory-secretrory products (Lockyer et al 2008;Zahoor et al 2014), and glycans shared with S. mansoni (Yoshino et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the morphological studies on haemocytes of Biomphalaria spp. (Lo Verde et al 1982;Barracco et al 1993;Cavalcanti et al 2012) (Anger & Granath 1995;Loker et al 2004;Sasaki et al 2005). Consequently, better understanding of the defence mechanism of O. hupensis could lead to information on cellular control of snails for evading attack by S. japonicum.…”
Section: Introductionmentioning
confidence: 99%